The Anti-inflammatory Effects of Short Chain Fatty Acids on Lipopolysaccharide- or Tumor Necrosis Factor α-Stimulated Endothelial Cells via Activation of GPR41/43 and Inhibition of HDACs - Li, Meng; van Esch, Betty C. A. M.; Henricks, Paul A. J.; Folkerts, Gert; Garssen, Johan (Frontiers in Pharmacology, 2018)
Background and Aim: Previously, we found that short chain fatty acids (SCFA) inhibit LPS or TNFα-induced endothelial inflammatory responses and excessive vascular cell adhesion molecule-1 (VCAM-1) expression, two important steps in the development of atherosclerosis. However, the mechanisms involved are still unclear. We hypothesized that the effects of SCFA are associated with activation of G-protein coupled receptor 41/43 (GPR41/43) and/or inhibition of histone deacetylases (HDACs). Methods: The expression and location of GPR41/43 and HDAC3 in human umbilical vein endothelial cells (HUVEC) were confirmed. HUVEC were pre-incubated with acetate, butyrate or propionate alone or in combination with GLPG0974 (GLPG, antagonist of GPR43) or β-hydroxybutyrate (SHB, antagonist of GPR41) and then exposed to LPS or TNFα. Interleukin (IL)-6 and IL-8 levels and VCAM-1 expression were measured. HDAC activity was measured after treatment with butyrate, propionate and trichostatin A (TSA, HDAC inhibitor). The peripheral blood mononuclear cell (PBMC) adhesive level was also determined after TSA treatment. Results: GPR41/43 were expressed on the membrane of HUVEC and HDAC3 was located in cytoplasm and nucleus. The GLPG and/or SHB treatments restored the inhibitory effects of acetate on IL-6 and IL-8 production and the inhibitory effects of butyrate or propionate on IL-6 production, but not on IL-8. In contrast, GLPG and/or SHB treatments did not affect the inhibitory effects of butyrate or propionate on TNFα-induced VCAM-1 expression. TSA showed similar effects on IL-8 production and VCAM-1 expression as butyrate and propionate. In addition, TSA significantly inhibited the adhesion of PBMC to an endothelial monolayer. Conclusion: Activation of GPR41/43 mediates the effects of acetate on IL-6 and IL-8 production and the effects of butyrate and propionate on IL-6 production. Furthermore, inhibition of HDACs mediates the effects of butyrate and propionate on IL-8 production, VCAM-1 expression, and PBMC adhesion to an endothelial monolayer. These data indicate the beneficial roles of SCFA in preventing vascular inflammation and relevant diseases by activation of GPR41/43 and inhibition of HDACs.